PEMENUHAN HAK ASASI MANUSIA ATAS LINGKUNGAN HIDUP YANG SEHAT - Fatma Ulfatun Najicha; Nugroho, Anastasha Ruth (Universitas Wiralodra, 2023)
The environment is an accumulation of the interaction of various factors contained in the biotic and abiotic environment. Juridically, it is constitutionally stated that a healthy environment is a form of human rights that must be fulfilled by the state. However, it is undeniable that currently there is a lot of damage to a healthy environment, which means that the state cannot fulfill its responsibilities. This paper will examine the definition of a healthy environment and how efforts to fulfill a healthy environment as part of human rights. This paper uses a normative juridical approach that refers to primary and secondary legal materials. With this approach, the results of the study state that a good and healthy environment is an environment that can allow humans to develop optimally, in harmony, harmony, and balance. Meanwhile, efforts to fulfill a healthy environment can be realized if the government and the community work together in realizing this right accompanied by law enforcement against a healthy environment. Keyword : healthy environment, human rights , law enforcement